The microstructure regulation, strengthening, toughening and hydrophilicity of polyamide6 in fabricating poly (vinylidene fluoride)-based flat membrane via the thermally induced phase separation technique. (5th March 2020) - Xiang, Shang; Guo, Zhenghua; Wang, Yuelin; Liu, Haihui; Zhang, Jing; Cui, Zhenyu; Wang, Hong; Li, Jianxin
Graphical abstract: Highlights: The addition of PA leads to cellular pore during the TIPS process. The mechanism of S-L phase separation combining slower pore-former and NIPS was proposed. The strengthening mechanism of particle, fiber and network fiber was proposed. PA can act pore-former and enhanced permeability and anti-fouling capacity. Abstract: The poly (vinylidene fluoride) (PVDF)/polyamide6 (PA6) flat blend membrane was prepared via thermally induced phase separation (TIPS) process using water-soluble diluent mixture. The function of PA6 to induce the non-solvent induced phase separation (NIPS) was disclosed for the first time and the membrane formation mechanism about S-L phase separation of TIPS by combining the pore-forming effect of PA6 and restricting PVDF crystallization to form somewhat opened cellular pore was proposed. The effect of PA6 on the microstructure of upper surface and matrix was discussed. The hydrophilicity, permeability, anti-fouling capability and anti-fouling mechanism of the membrane were investigated. Interestingly, the morphology of PA6 within the matrix changed from the dispersed phase (particle or fiber) to the continuous phase (network fiber) with the addition of PA6, which in turn increased the breaking strength or breaking elongation and the corresponding mechanisms of strengthening and toughening were developed from the point of crystal particle, fiber and network fiber, respectively. Also, the introduction of PA6 reduced the shrinkage of the membrane, increased the porosity and hydrophilicity, improved the rejection to petroleum ether-in-water emulsion and Congo Red (CR), and enhanced the anti-fouling capacity. This work disclosed the functions of water-insoluble hydrophilic polymer to induce the mass-transfer, pore-forming effect by combining the S-L phase of TIPS and NIPS during the membrane formation process for the first time, presented sample and effective method to tailor the microstructure of membrane and enhance the mechanical property, permeability of membrane via the combination of TIPS and polymer blending for water treatment.